In Silico Analysis of Active Compounds from Allium tuberosum as Drug Candidate for Inhibitor DENV-3 Envelope Protein - Nuryady, Moh Mirza; Juliana, Levina Imelda; Ariesaka, Kiky Martha (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2024)
Dengue fever has become a global health issue, the development of dengue vaccine has not yet been established. Medicinal plants are an ideal alternative for DENV infection drugs. The purpose of this study was to determine in silico the potential of active compounds from Allium tuberosum as envelope protein inhibitors of DENV-3. The method of this research is to do docking analysis of compounds with DENV-3 envelope protein and analysis of amino acid residues using MVD, pharmacokinetic analysis using SwissADME, toxicity analysis using ProTox-II. The best docking value for the potential activity to inhibit the receptor DENV-3 is the thymidine compound (RS: -81.1245 kcal/mol). The highest activity of thymidine is the most promising as a drug candidate, as evidenced by the toxicity analysis which is predicted to have non-carcinogenic, non-mutagenic, inactive properties against hepatotoxicity, cytotoxicity and immunotoxicity parameters, as well as pharmacokinetic analysis that fulfills 6 parameters of lipopolicity, molecular weight, polarity. , insolubility, insaturation, and flexibility which indicate the drug candidate of thymidine is safe for its bioavailability. The conclusion from the results of this study is that one compound has the ability as an antiviral, binding score with DENV-3 is good, and is safe in terms of pharmacokinetics and toxicity, namely thymidine compound.